Minimize Mental Workload and Fatigue of Horizontal Directional Drilling Worker Using Rating Scale Mental Effort and Swedish Occupational Fatigue Inventory Methods. - Septiani, Winnie Septiani; Rusy, Rafif Irfansyah Putra Rusy; Adisuwiryo, Sucipto Adisuwiryo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
Horizontal Directional Drilling (HDD) is a drilling technique that does not damage the groundsurface; the HDD process involves a stage that requires high concentration and physical skills and isoften carried out in challenging working conditions, causing mental Workload and fatigue in HDDworkers. HDD workers should be given improvements in their work methods to be safe whenworking due to being too tired or losing focus. HDDs must be monitored in real-time, which requiresworkers to get good results without errors so that workers experience workload pressure andmental fatigue. This study aims to measure and minimize mental Workload and fatigue in HDDworkers and determine improvement proposals based on the why-why diagram. Mental workloadmeasurement using the RSME method and fatigue using SOFI and why diagrams are used to findcause and effect in mental Workload and fatigue experienced by HDD workers. Based on the analysisof RSME, the scale value obtained based on six indicators of WL, WD, WP, WME, WA, and WF is 92.05,which is in the category of enormous business carried out, and the KiK indicator or fatigue gets thehighest scale value of 106.52 with the business category given is very large so that HDD workersexperience a mental workload. Mental workload and fatigue correlate. Based on the results of SOFI,the sleepiness dimension received a score of 21.83 with a high level of fatigue category. Therefore,the proposed improvement to the causal results of the Why Diagram is adding the workforce,adjusting work shifts, and monitoring and evaluating HDD workers.